Influential Factors on the Stress Level Among Students of Bachelor’s Degree in Nursing (International Journal of Nursing Education, 2021)
Background: Stress is very common among students belonging to the healthcare domain. They are moreexposed to stressful factors than the rest of the student community. It is of extreme importance to evaluatethe level of stress among the students of the bachelor’s degree in Nursing, as well as to know the factorsinvolved. Method: Study quantitative, descriptive scope, and cross-sectional. The academic stress level wasmeasured on 332 students from different semesters of the bachelor’s degree in Nursing, through of the shortversion of the “About Stress in University Students questionnaire”. Conclusion: 218 of nursing studentsexperienced stress levels. The average value of stress was 34.59 ± 15.49. The main influential factors on thestress level were somatization and anxiety, followed by induced stress by third parties and workload. Therewere statistically significant differences in somatization and anxiety between women and men (p
Keywords: nursing, Stress, stressful factors, students.